A Comment on "The Valuation of R&D Firms with R&D Limited Partnerships." - Cheung, Joseph K.; Li, Mandy (The Accounting Review, 1992)
Comments on the article titled, `The Valuation of R&D Firms with R&D Limited Partnerships,' by Terry Shevlin to clarify his interpretation of the components of the research and development (R&D) limited partnership (LP) as a call option reflected in the firm's stock price. Criticism on the measurement of the asset and liability components of the LP in the option pricing network.